Prevalence and pattern of post COVID-19 health problems among adults attending post COVID-19 clinics of selected tertiary care centres in Kolkata - Adhikari, Uma Rani; Patra, Manju (International Journal Of Community Medicine And Public Health, 2025)
Background: Post COVID-19 health problem is the persistence of signs and symptoms that develop during or after COVID-19 infection for more than 12 weeks and are not explained by an alternative diagnosis. This study aimed to determine the prevalence and pattern of post COVID-19 health problems in adults of post COVID -19. Methods: A descriptive cross-sectional survey was conducted in post COVID-19 clinic of two tertiary care government sectors in Kolkata. Data collected through pre tested interview schedule and record analysis from the patients with COVID-19 positive through SARS-Cov-19, RT-PCR positive or rapid antigen positive test. Data collected from 150 post COVID-19 patients after ethics committee approval. All data were analysed using SPSS version 19. Results: More than 3/4th of the participants (77.3%) had reported post COVID-19 health problems and majority (43.3%) of the subjects had fatigue, 30% of the subjects had joint pain 28.67% of the subjects had cough. Majority (65.1%) of the subjects had mild illness during their COVID-19 infected period and 25% had other health problems among them maximum (40%) of the subjects had interrupted sleep, 28% of the subjects had uncomfortable in walking and (6%) of the patients had depression. Less common health problems were hematuria (4%), blurred vision (4%) and anosmia (4%). 21.5% participants reported ≥7 post COVID-19 health problems among all participants. Conclusions: The present study reveals that the commonest health problems in post COVID-19 patients were fatigue, headache, joint pain, shortness of breath. Comprehensive rehabilitation program and monitoring is essential for management.